Semiempirical method for process analysis on electric arc spray forming of Fe-0.06%C steel rings - Seok, HK; Llewellyn, HJ; Lee, JC; Grant, PS (TAYLOR & FRANCIS LTD, 2002)
A numerical program, which calculates the temperature profiles of electric are spray formed (EASE) preforms, is coded on the basis of a shape forming model, droplet flight dynamics, and the boundary fitted coordinate (BFC) method for the calculation of heat transfer equations. Some thermophysical input data for the calculations, such as average droplet temperature impinging on the deposit surface, effective thermal conductivity of the deposit, and heat transfer coefficient at the interface and surface, are given by matching the experimental results with the numerical calculation results. Using the program, the temperature changes of the Fe-0.06%C steel ring deposit during the EASF process are calculated. The effects of the EASF parameters, such as substrate rotation velocity, average droplet temperature, and wire feedrate, on the temperature changes of the Fe-0.06%C steel ring preforms are a so estimated. PM/0951 At the time the work was carried out Dr Seok (drstone@kist.re.kr), Mr Llewellyn, and Dr Grant were with the Oxford Centre of Advanced Materials and Composite, Oxford University, Parks Road, Oxford, OX1 3PH, UK, and Dr Lee was with Division of Materials, Korea Institute of Science and Technology, 136-791, Seoul, Korea. Dr Seok is now with Korea Institute of Science and Technology, 136-791, Seoul, Korea. Manuscript received 6 February 2002; accepted 22 November 2001. (C) 2002 IoM Communications Ltd.
Keywords: HEAT-TRANSFER; THERMAL HISTORIES; FLUID-FLOW; SOLIDIFICATION; MICROSTRUCTURE; TEMPERATURES; DROPLETS; BEHAVIOR; MODEL